Development of Interactive Multimedia Articulate Storyline 3 Based on Problem Based Learning on Atomic Structure Materials Oriented to Students' Critical Thinking Skills - Dwi Asri; Haryanto Haryanto; Asrial Asrial; Zurweny Zurweny; Febbry Romundza; Asmiyunda Asmiyunda (Universitas Khairun, 2026)
This study aims to determine the process of development, feasibility, and response of teachers and students to interactive multimedia Articulate Storyline 3 based on problem-based learning on atomic structure materials oriented to students' critical thinking skills. The product development process is carried out by the Lee and Owens model stages, namely: analysis, design, development, implementation, and evaluation. The instruments used were interview sheets and questionnaires. The resulting products are validated by material experts and media experts. Furthermore, it is assessed by teachers and tested in a one-to-one and small group manner. Data analysis techniques are used for qualitative data analysis and quantitative data analysis. The results of the study that the product developed was conceptually and procedurally feasible based on subject matter experts obtained a percentage of 90%, a one-to-one test with a percentage of 90%, and from the student's response had a percentage of 91.7%. Based on the results of the study, it can be concluded that interactive multimedia Articulate Storyline 3 based on problem-based learning on atomic structure materials oriented to students' critical thinking skills has fulfilled all stages with